LEARNING STRATEGIES TO IMPROVE SPEAKING SKILLS OF INFORMATICS STUDENTS - Marita Nurharjanti; Rosyidah Jayanti Vijaya; Agus Wibow; Netci Hesvindrati (Bajang Institute, 2025)
This research aims to identify the learning strategies used to improve English speaking skills by Informatics students of Universitas Amikom Yogyakarta. The necessity of studying speaking skills has been highlighted by a lot of researchers in recent years. This research used questionnaires of Language Learning Strategies (SLL) to collect the data. The research respondents were 22 students of the academic year 2023/2024 from an international class of Informatics Study Program, Faculty of Computer Science. They were divided into three categories; seven students with high English speaking skills, eight students with medium English speaking skills, and seven students with low English speaking skills. This study employs a quantitative research method with a Linear Regression Analysis to explore the learning strategies used to improve speaking skills among Informatics students. The strategies are divided into 6: Affective Strategy, Cognitive Strategy, Social Strategy, Meta-Cognitive Strategy, Memory Strategy and Compensation Strategy. The result showed that students with high speaking skills implement the social strategy. It gives high influence to the success of their speaking skills. The students from medium level use the cognitive strategy. Whereas the students with low speaking skills also implement the cognitive strategy but in low frequency.